DEVELOPMENT OF LONG AND SQUARE LEARNING DEVICES WITH A REALISTIC MATHEMATICAL APPROACH BASED ON BRUNER THEORY FOR STUDENT CLASSY VII SMP NEGERI 1 PALOPO - Anita Prima (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2013)
The research question was how is the process and the result of learning device of rectangle and square through realistic mathematics approach based Bruner theory to student of grade VII at SMPN 1 Palopo. This study was research and development ( R & D) because it aimed to produce the learning device of rectangle and square through realistic mathematics approach based Bruner theory. The learning device consisted of (1) lesson planning, (2) teacher’s manual, and (3) student’s worksheet. The learning device model which employed in this study referred to 4-D Thiagarajan, Semmel & Semmel model which consisted of the defining stage, designing stage, development stage, and dissemination stage. This study was conducted in grade VII.d at SMPN 1 Palopo with 26 students. The result obtained was learning device which was practical and effective, student’s activity was as expected, the application of learning device was in implemented category and student’s response was in positive category. After conducting the development stage, the learning device of rectangle and square with realistic mathematics approach based Bruner theory was in good quality. Student’s activity in group work was focused on the LKS completion and discussion among students. Students academic competence in learning by employing realistic approach based Bruner theory was improved and the score variation of academic achievement between students who had high competence, fair competence, and low competence after the learning was gradually smaller